The Legal Status of Lawful Landowners and Legal Protection in Land Possession Disputes Without Rights Under National Agrarian Law (Lembaga Pengembangan Kinerja Dosen, 2026)
Land ownership disputes without rights are a common land issue that disrupts legal certainty for legitimate landowners. Although the national land law system has regulated land registration and the issuance of certificates as forms of legal protection, in practice conflicts are still found between physical possession and legal ownership. This research aims to analyze the legal status of the rightful landowner and the forms of legal protection in land ownership disputes without rights. The research method used is normative legal research with a statutory approach and a conceptual approach, examining Law Number 5 of 1960 concerning Basic Agrarian Regulations, Government Regulation Number 24 of 1997, and Government Regulation Number 18 of 2021. The research results show that land ownership certificates have strong evidentiary power and place the legitimate landowner in a more protected legal position, while unauthorized land possession does not gain legal legitimacy and can be qualified as an unlawful act. Therefore, legal protection for legitimate landowners must be consistently enforced to achieve legal certainty and justice in the field of land ownership.